POSTMODERNISMUL: ÎNTRE ONIRISM ȘI METALITERATURĂ - MANOLE, Lilia (BIBLIOPOLIS, 2020)
This study recorded one of three science that deals with literature and literary history. The author aims to open a new aspect in the evolution of Romanian literature, focusing the research on postmodern period, so much in vogue today, and the elements that sometimes we disagree. The analysis contains the transformation of literary facts, finding certain keys, solutions, social repercussions of contemporary literary fact.